2021
DOI: 10.1186/s12884-021-04103-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prophylactic balloon occlusion of internal iliac artery in pregnancies complicated by placenta previa and accreta

Abstract: Background Placenta previa and accreta are serious obstetric conditions that are associated with a high risk of intraoperative massive hemorrhage, the prophylactic intravascular balloon occlusion technique is increasingly used in managing uncontrolled hemorrhage in cesarean section (CS). We aim to examine the clinical effectiveness of prophylactic balloon occlusion of the internal iliac artery (PBOIIA) during CS in improving maternal outcomes for patients with placenta previa and accreta. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…However, length of hospitalization after surgery as well as ICU admission were comparable. In contrast to our study another study Chen et al [15] suggested that Prophylactic internal iliac artery balloon occlusion has no significant effect on reducing hysterectomy rate in patients with placenta previa and accreta, although it could reduce the intraoperative blood loss in patients with massive haemorrhage but it significantly increases the financial cost for patients. Therefore, it should not be routinely recommended to patients with placenta previa and accreta.…”
Section: Discussioncontrasting
confidence: 99%
“…However, length of hospitalization after surgery as well as ICU admission were comparable. In contrast to our study another study Chen et al [15] suggested that Prophylactic internal iliac artery balloon occlusion has no significant effect on reducing hysterectomy rate in patients with placenta previa and accreta, although it could reduce the intraoperative blood loss in patients with massive haemorrhage but it significantly increases the financial cost for patients. Therefore, it should not be routinely recommended to patients with placenta previa and accreta.…”
Section: Discussioncontrasting
confidence: 99%
“…Placenta previa and placenta accrete spectrum, which acts as the strongest predictor for PPH, may result in severe PPH or even a hysterectomy ( 30 , 31 ). In recent years, intravascular balloon occlusion has become an increasingly popular prophylactic measure, which includes intravascular balloon occlusion of the abdominal aorta or internal iliac arteries ( 32 36 ). During the surgery, the abdominal aorta/internal iliac artery can be temporarily blocked by the balloon, thus reducing the uterine artery's blood supply, and the hemostatic procedures can be simplified and shortened.…”
Section: Discussionmentioning
confidence: 99%
“…9 According to recent studies, the effectiveness of intraoperative internal iliac artery balloon occlusion in women with PAS was not reliable. 10,11 Therefore, most of the women in our study who had bilateral internal iliac artery balloon occlusion were delivered before the year 2020. After 2020, prophylactic balloon occlusion of the internal iliac artery was not routinely conducted in our hospital, and prophylactic abdominal aortic balloon was performed in some severe cases of PPA at the multidisciplinary team's discretion.…”
Section: Methodsmentioning
confidence: 98%